Self-diffusion of molecules in water-ethanol solutions of low concentration. Neutron data - Vasylkevych, O.A.; Slisenko, V.I. (Reports of the National Academy of Sciences of Ukraine, 2019)
The work is devoted to the abnormal behavior of dilute wateralcohol solutions. The dynamics of molecules of the waterethanol system, depending on the concentration at 281 K, is researched by the method of quasielastic scattering of slow neutrons. The total selfdiffusion coefficient of molecules D, its singleparticle Ds-p and collective Dcoll components, and the time of settled molecule’s life in the oscillating state t0 are determined. The region of small concentrations was studied in detail, and two minima in the coefficients D and Ds-p were detected in the vicinity of concentrations X = 0.04 mol.f. and X = 0.2 mol.f. Time t0 at these concentrations is increasing significantly. This indicates a significant decrease in the intensity of the activation mechanism of diffusion of molecules, which is quite possible due to the binding of water and ethanol molecules into complexes (clusters).